Effect of frontline demonstrations on yield and economics of tomato (Lycopersicon esculentum) in Rajasthan, India (Current Horticulture, 2024)
The study was carried out to find out the effect of frontline demonstrations on yield of tomato (Lycopersicon  esculentum Mill.) at Krishi Vigyan Kendra, Banswara, MPUAT, Udaipur, during 2013-14 to 2016-17 at farmers’ fields in different locations of Banswara district. A total 40 demonstrations were conducted at 40 farmers’ fields on 8.0 ha lands. Each frontline demonstration was laid out on 0.2 ha area, while adjacent 0.2 ha was considered as the control (farmers’ practices). The selection of farmers was done on basis of survey by KVK and special training was organized for selected farmers on tomato cultivation. For the demonstration plot all the recommended package of practices like the use of biocontrol agents (Trichoderma and Pseudomonas) enriched FYM, recommended dose of fertilizers and integrated pest management practices, use of quality seed of improved variety etc. were followed.